2019
DOI: 10.1186/s42483-019-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals the unique evolutionary status of Plasmodiophora brassicae and the essential role of GPCR signaling pathways

Abstract: Plasmodiophora brassicae is an important biotrophic eukaryotic plant pathogen and a member of the rhizarian protists. This biotrophic pathogen causes clubroot in cruciferous plants via novel intracellular mechanisms that are markedly different from those of other biotrophic organisms. To date, genomes from six single spore isolates of P. brassicae have been sequenced. An accurate description of the evolutionary status of this biotrophic protist, however, remains lacking. Here, we determined the draft genome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
(79 reference statements)
0
20
0
Order By: Relevance
“…Fine-tuning between plant immune response and microbe genomic traits is known to regulate endophytic colonization (Trivedi et al, 2020). Interestingly, the cell-surface G-protein-coupled receptors (GPCRs) mediated signalling pathway are significantly enriched in the Rhizaria supergroup (Bi et al, 2019). GPCRs sense a diverse array of extracellular signals from plant host and are reported to promote endophytic colonization (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fine-tuning between plant immune response and microbe genomic traits is known to regulate endophytic colonization (Trivedi et al, 2020). Interestingly, the cell-surface G-protein-coupled receptors (GPCRs) mediated signalling pathway are significantly enriched in the Rhizaria supergroup (Bi et al, 2019). GPCRs sense a diverse array of extracellular signals from plant host and are reported to promote endophytic colonization (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bi et al . (2019) showed that P. brassicae is able to have perception of external signals thanks to specific signalling pathway and to adapt to its environment. In our study, the very early step of interaction between P. brassicae spores and soil microbiota was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…During both the spore germination and the primary zoospore stages, the pathogen showed high active metabolisms of chitinous cell wall digestion, starch, citrate cycle, pentose phosphate pathway, pyruvate, trehalose, carbohydrates and lipids (Schwelm et al ., 2015a; Schwelm et al ., 2015b; Bi et al ., 2016). During the second phase of infection, genes involved in basal and lipid metabolism were highly expressed (Bi et al ., 2016), as well as the G‐protein‐coupled receptors pathway‐related genes (Bi et al ., 2019). These active metabolic pathways allow P. brassicae to take up nutrients from the host cells (Kageyama and Asano, 2009; Perez‐Lopez et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The signalling pathway of GPCRs is spread through the whole living kingdom (de Mendoza et al ., ), e.g. it has been demonstrated that diatoms sense the presence of predators via the GPCR signal transduction pathway (Amato et al ., ) and that in the rhizarian protist Plasmodiophora brassicae GPCR signal transduction pathways underwent a robust expansion and plays a pivotal role in the germination of resting spores (Bi et al ., ). Furthermore, in oomycetes a very peculiar GPCR system evolved (Meijer and Govers, ).…”
Section: Discussionmentioning
confidence: 97%